Relationship-Centered Advising in a Medical School Learning Community. (February 2019) - Frosch, Emily; Goldstein, Mitchell
Background: Medical schools are required to have formal advising structures; however, there are limited data on how to optimally meet that mandate. Learning communities (LC), with their emphasis on longitudinal relationships, offer a unique scaffold for advising. Program description: The Johns Hopkins School of Medicine (JHSOM) LC focuses on curricular and extracurricular longitudinal connections between students and advisors. A core component of the LC is a relationship-centered advising (RCA) model drawing from best practices in physician–patient relationships, life coaching, and social contract theories. The key elements of the model include dyadic and small group advising, while the LC structure allows for faculty development in these domains. Relationship-centered advising approaches the collaborative advising work between students and advisors through explicit valuing of personal experiences, mutual respect, and earned trust. Framing the advising relationship in this way allows it to grow with the student along their medical school journey. Program evaluation & results: Student and faculty satisfaction with this model is high. Data from annual, anonymous student evaluations consistently indicate high degree of trust in and satisfaction from these relationships. Discussion: Relationship-centered advising aims to create a relationally anchored platform on which students can develop their personal and professional identities. This LC-based advising model is adaptable across schools regardless of structure and resources.